Carnitine PT II Deficiency and Cerebral Dysgenesis - J Gordon Millichap (Pediatric Neurology Briefs)
A newborn female infant with neonatal lethal multiorgan carnitine palmitoyltransferase II (CPT II) defiency is reported from the Departments of Medicine and Pathology, Children’s Hospital, Boston, MA; and the Department of Pharmacology and Medicine, Case Western Reserve University, VA Medical Center, Cleveland, OH.